Supervisory fault tolerant controlwith integrated fault detection and isolation: a switched system approach - Yang, Hao; Jiang, Bin; Cocquempot, Vincent; Lu, Lingli (Zielona Góra: Uniwersytet Zielonogórski)
This paper focuses on supervisory fault tolerant control design for a class of systems with faults ranging over a finite cover. The proposed framework is based on a switched system approach, and relies on a supervisory switching within a family of pre-computed candidate controllers without individual fault detection and isolation schemes. Each fault set can be accommodated either by one candidate controller or by a set of controllers under an appropriate switching law. Two aircraft examples are included to illustrate the efficiency of the proposed method.
Keywords: fault tolerant control; fault detection and isolation; switching control; switched systems